Extracellular Vesicles and Micro-RNAs in Liver Disease - Washington, Alexander M.; Kostallari, Enis (Seminars in Liver Disease, 2024)
Progression of liver disease is dependent on intercellular signaling, including those mediated by extracellular vesicles (EVs). Within these EVs, microRNAs (miRNAs) are packaged to selectively silence gene expression in recipient cells for upregulating or downregulating a specific pathway. Injured hepatocytes secrete EV-associated miRNAs which can be taken up by liver sinusoidal endothelial cells, immune cells, hepatic stellate cells, and other cell types. In addition, these recipient cells will secrete their own EV-associated miRNAs to propagate a response throughout the tissue and the circulation. In this review, we comment on the implications of EV-miRNAs in the progression of alcohol-associated liver disease, metabolic dysfunction-associated steatohepatitis, viral and parasitic infections, liver fibrosis, and liver malignancies. We summarize how circulating miRNAs can be used as biomarkers and the potential of utilizing EVs and miRNAs as therapeutic methods to treat liver disease.
Keywords: liver disease; EVs; miRNA; therapeutics; biomarkers